Penerapan Pembelajaran Berbasis Podcast untuk Mendukung Literasi Mendengar Siswa SD - Rizky Maulana; Salsabila Rahmawati; Taufik Hidayat (Gema Cendekia Institute, 2026)
This study aims to analyze the application of podcast-based learning to support elementary school students' listening literacy. Listening literacy is an important foundational skill in the learning process because it plays a role in developing students' language comprehension, concentration, and critical thinking skills. However, in practice, listening skills often receive less attention than reading and writing skills. Therefore, learning innovations are needed that can improve students' listening skills more effectively. This study used a quantitative approach with a quasi-experimental design using a pretest-posttest model. The study subjects consisted of two classes: an experimental class that received podcast-based learning and a control class that used conventional learning methods. Data were collected through listening literacy tests (pretest and posttest), student response questionnaires, and documentation of the learning implementation. The results showed that the application of podcast-based learning significantly improved students' listening literacy skills in the experimental class. Students were better able to grasp main ideas, understand detailed information, and summarize the content of the audio material they listened to. Furthermore, student responses to the use of podcasts also showed positive results, particularly in aspects of learning motivation, attention focus, and engagement in class discussions. Despite challenges such as differences in vocabulary comprehension and audio speed, podcasts are still considered an innovative and effective learning medium that is relevant for elementary schools. With structured lesson planning, podcasts have the potential to continuously improve students' listening literacy.